LEGAL PROTECTION FOR HEIRS OF DIGITAL ASSETS IN INDONESIA'S SPECIAL INHERITANCE REGULATIONS - Angelin Lonata A; Yusuf Daeng; Silm Oktapani (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
The rapid development of information and communication technology has led to the emergence of various forms of digital assets with economic value, including social media accounts, cryptocurrency wallets, blockchain-based digital assets, digital banking accounts, and other electronic data. However, the inheritance of digital assets has not yet been specifically and comprehensively regulated within the Indonesian inheritance law system. This situation creates legal uncertainty for heirs in exercising their rights over the digital assets left by the deceased. This study aims to analyze the legal framework governing digital asset inheritance in Indonesia and to examine the forms of legal protection available to heirs regarding digital assets left by the predecessor. The research employs a normative legal research method using statutory, conceptual, and comparative approaches. Data were collected through library research involving legislation, legal literature, and other legal documents related to digital assets and inheritance law. The findings indicate that regulations concerning digital asset inheritance in Indonesia remain fragmented and have not provided adequate legal certainty for heirs. Legal protection for heirs of digital assets can be achieved through the recognition of digital assets as inheritable property, the establishment of specific regulations governing digital asset inheritance, and the provision of clear mechanisms for access and transfer of rights to heirs. Therefore, reform of inheritance law that is responsive to technological developments is necessary to ensure legal certainty, justice, and legal protection for heirs of digital assets in Indonesia.